(untitled) - Maria Helena Almeida; Alejandro Orgambídez; Carina Martinho Santos (University of Ostrava, 2020)
Aim: According to the health organization model: 1) social resources in the working group (e.g. social support) and structural resources for the execution of tasks (e.g. autonomy) are correlated with 2) healthy, active professionals experiencing high levels of psychosocial well-being through job satisfaction. This study examines to what extent social resources in the work group (supervisor and peer social support) and employees' perception of global empowerment correlate with job satisfaction. Design: A cross-sectional and exploratory study of a descriptive and correlational nature. Methods: Following a quantitative methodology, a structural equation model was created, processed by Stata software. This study comprised a convenience sample of 370 Portuguese healthcare professionals working in five-star private hospitals, and aimed to examine the relationship between social support, global empowerment, and job satisfaction. Data were gathered from physically administered questionnaires. Results: Job satisfaction was significantly predicted by social support and global empowerment (direct and indirect effects). Conclusion: The results support the health organization model, indicating that positive outcomes, such as job satisfaction, can be predicted by perceptions of social resources (social support) and structural resources (global empowerment), but also that perceptions of global empowerment play a mediating role between perceived social support and job satisfaction.